2015
DOI: 10.1007/s11205-015-1139-7
|View full text |Cite
|
Sign up to set email alerts
|

A New Multidimensional Measure of Development: The Role of Technology and Institutions

Abstract: This paper constructs four structural indices by using 42 socioeconomic variables for 129 countries and the 10 years period from 2003 to 2012. Each structural index can be considered as a measure of a certain dimension of development. The first two indices are the most useful in explaining gaps in development across countries. The first captures the role of technology and institutional quality while the second provides a measure of the basic level of development. The contrast between them signifies that the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Based on previous research findings, it was found that the main dimensions of a multidimensional composite index for measuring regional development should include the knowledge accumulation, quality of life, and underlying health levels of societies [33] (p. 4). Thus, also taking into account the dimensions used and presented previously by Ganegodage et al [32], we consider that the five dimensions defined by us are relevant and appropriate for a regional analysis of the development in a Central and Eastern European country, and the selected indicators are also valid for a longer period of time. However, the specific selection of indicators for each dimension (sub-index) was established with multivariate statistical methods from a larger variable list, which are available in a territorial range for a longer period of time.…”
Section: Romanian Regional Development: Previous Methods and Analysesmentioning
confidence: 98%
See 2 more Smart Citations
“…Based on previous research findings, it was found that the main dimensions of a multidimensional composite index for measuring regional development should include the knowledge accumulation, quality of life, and underlying health levels of societies [33] (p. 4). Thus, also taking into account the dimensions used and presented previously by Ganegodage et al [32], we consider that the five dimensions defined by us are relevant and appropriate for a regional analysis of the development in a Central and Eastern European country, and the selected indicators are also valid for a longer period of time. However, the specific selection of indicators for each dimension (sub-index) was established with multivariate statistical methods from a larger variable list, which are available in a territorial range for a longer period of time.…”
Section: Romanian Regional Development: Previous Methods and Analysesmentioning
confidence: 98%
“…Research questions. Starting from the dimensions used by Ganegodage et al [32], and from the methodological and content considerations on cultural areas formulated by Sandu [35,36], and also considering Jongh and Meyer's [9] caution and the advice of Greco et al [45] on subjective weighting (he warns us to be cautious when constructing-combining and using multidimensional composite indices, because of the subjective weightings or other subjectivities included in the methodology), as well as Periši and Wagner's [44] (p. 207) recent findings on the advantages of multidimensional methods, this research tries to answer the following questions:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we included the following variables to operationalize the institutional development of a country: control of corruption (Mungiu and Harmann, 2019), government effectiveness (Ahmad and Saleem, 2014), political stability (Waterbury, 1976; Altun, 2016) and absence of violence (Buvinic and Morrison, 1999; Bowman et al , 2008), regulatory quality and rule of law (Boettke and Subrick, 2003; Ganegodage et al , 2017), and voice and accountability (Goetz and Jenkins, 2002). We also used directly related institutional parameters for franchising, such as specific laws and the number of days required to start a business.…”
Section: Methodsmentioning
confidence: 99%
“…We also used directly related institutional parameters for franchising, such as specific laws and the number of days required to start a business. Finally, we considered variables related to infrastructure, such as access to electricity and water, fixed broadband access, and cellphone subscriptions (Ganegodage et al , 2017).…”
Section: Methodsmentioning
confidence: 99%